The Effect Of Generative Learning Strategy Of Cognitive Learners (Controlled - Flexible) On The Development of Some Artistic Skills Accuracy Young Volleyball Players - Kahlil, Reiad; Mohammed, Jassim (Journal of Physical Education, 2018)
The Effect Of Generative Learning Strategy Of Cognitive Learners (Controlled - Flexible) On The Development of Some Artistic Skills Accuracy Young Volleyball PlayersThe importance of research lies in the diversity in the learning process is based on the learning strategy by involving the player in generating new ideas based on his previous experiences and to benefit from in volleyball performance. The problem of the research lies in the researcher being a former volleyball player of this age group and noted that many of the coaches use traditional, old fashioned teaching styles. Thus the researchers aimed at designing a teaching program using cognitive learning (controlled – flexible) to develop the artistic skills in volleyball as well as identifying the effect of this teaching program on the development the artistic skills in volleyball. The researchers used the experimental method. The sample was (48) while the subjects were (28) young volleyball players aged (12 – 14) years old from the national center for gifted in volleyball. The data was collected and treated using proper statistical operations. The researchers concluded that the teaching program is very effective in developing the accuracy of performing the three skills understudy with differences. Finally they recommended using the teaching program in developing of some of the skills of the volleyball players of the ages (12-14) because of its active role in the development of the variables understudy for players with the cognitive method (controlled – flexible).